THE EFFECTIVENESS OF USING COMMUNICATIVE APPROACH IN TEACHING THE SIMPLE PAST TENSE AT SMPN 12 BATAM - Suswanto Ismadi Megah; Dede Afifah (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
This study was aimed to identify t The Effectiveness of Using Communicative Approach in Teaching the Simple Past Tense. This research employed quantitative research method. The design of the collecting the data that used in research are, questioner method, test method, library method, observation method and interview method. This research was conducted at class of second year students of SMPN 12 Batam in the academic year 2018/2019.  As for the time the researched held on 31 March 2019 until 25 May 2019. In this research, the populations of the study were students in second year students at SMPN 12 Batam in the academic year 2018/2019. There were  students from two classes, whereas the samples are 62 students, where 30 students from class VIII-4 (control class) and 32 students from VIII-5 ( the experiment class). This research was concluded that the effectiveness of using communicative approach in teaching the simple past tense: A case study of second year students at SMPN 12 BATAM in the academic years 2018/2019. The result was the calculation of the t-test, it was obtained that the t-observed was 5.506 and t-table was 2.042 at the level of significant 0, 05. It was obtaining that t- observed t-table, it means the alternative hypothesis (Ha) was accepted and Ho rejected.